1979
DOI: 10.1128/aac.16.6.823
|View full text |Cite
|
Sign up to set email alerts
|

Fortimicin A: collaborative in vitro susceptibility. Comparison with amikacin and gentamicin against 11,840 clinical bacterial isolates

Abstract: The susceptibility of 11,840 clinical bacterial isolates to fortimicin A was determined by agar dilution or broth microdilution methods and compared with their susceptibility to amikacin and gentamicin. In general, the in vitro activity of fortimicin A was essentially the same as that of amikacin. Significant exceptions were the increased effectiveness of fortimicin A against Serratia marcescens and the greater activity of amikacin against Pseudomonas and other nonfermentative gram-negative bacilli. On a weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
13
1

Year Published

1980
1980
1986
1986

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 10 publications
3
13
1
Order By: Relevance
“…Fortimicin A MICs are, therefore, generally higher than MICs of gentamicin, netilmicin, sisomicin, and tobramycin. These results are in general agreement with previous reports (4,5). We found in this study, as was found in the collaborative study of Jones et al (5), that fortimicin A and amikacin were more active against P. stuartii than was gentamicin.…”
Section: Materlals and Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…Fortimicin A MICs are, therefore, generally higher than MICs of gentamicin, netilmicin, sisomicin, and tobramycin. These results are in general agreement with previous reports (4,5). We found in this study, as was found in the collaborative study of Jones et al (5), that fortimicin A and amikacin were more active against P. stuartii than was gentamicin.…”
Section: Materlals and Methodssupporting
confidence: 83%
“…This collection of organisms was assembled for the purpose of challenging this aminoglycoside with a wide range of species and of resistance patterns without regard to usual distribution, as described previously (10 The inocula were prepared from actively growing broth cultures, which were adjusted to match the turbidity of a 0. 5 McFarland standard (7), and were diluted 1:50 in sterile distilled water containing 0.02% Tween 80. Disposable inoculators were used to inoculate the microdilution trays with these adjusted inocula; the final inoculum was approximately 105 colony-forming units (CFU) per ml.…”
Section: Materlals and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortimicin A, the most active naturally occuring member of this class, has antimicrobial activity similar to that of amikacin, but lacks significant activity against Pseudomonas aeruginosa (3,7,12).…”
mentioning
confidence: 99%
“…1, compound 1), the major component of the fortimicin complex, has high, broad-spectrum antibacterial activity (2,4). In addition, fortimicin A has remarkable activity against a wide variety of microorganisms resistant to many of the pseudotrisaccharide aminoglycoside antibiotics (4).…”
mentioning
confidence: 99%